Diagnose Sexuelle Des Os Coxaux Archéoanthropologiques Issus De L’amas Coquillier De Songon Kassemblé Au Sud-Est De La Côte d’Ivoire - Coulibaly Daouda (European Scientific Journal, ESJ, 2016)
Since 2008, some surfaces gatherings have been done on the archaeological shells middens of Songon Kassemblé in Ivory Coast. As a result, several pieces of anthropological bones have been collected. Each collection with a minimum of three individuals, contains some skulls, some longs bones of the uppers and the inferiors members, and some hips bones. These bones are the main material for experimentation. In fact, determing the sex is the purpose of this work. To do so, firstly we will estimate the age of the hips bone owners at the time of their death. Secondly morphoscopical and morphometrical methods has been used. The results are, the sex of three hips bone owners is female and the last one sex is indeterminate.